Catalytic Asymmetric Dearomatization by Visible‐Light‐Activated [2+2] Photocycloaddition. (27th April 2018) - Hu, Naifu; Jung, Hoimin; Zheng, Yu; Lee, Juhyeong; Zhang, Lilu; Ullah, Zakir; Xie, Xiulan; Harms, Klaus; Baik, Mu‐Hyun; Meggers, Eric
Abstract: A novel method for the catalytic asymmetric dearomatization by visible‐light‐activated [2+2] photocycloaddition with benzofurans and one example of a benzothiophene is reported, thereby providing chiral tricyclic structures with up to four stereocenters including quaternary stereocenters. The benzofurans and the benzothiophene are functionalized at the 2‐position with a chelating N ‐acylpyrazole moiety which permits the coordination of a visible‐light‐activatable chiral‐at‐rhodium Lewis acid catalyst. Computational molecular modeling revealed the origin of the unusual regioselectivity and identified the heteroatom in the heterocycle to be key for the regiocontrol. Abstract : Chemie mit Blaulicht : Eine katalytische asymmetrische Dearomatisierung von Benzofuranen und einem Benzothiophen gelingt mithilfe einer durch sichtbares Licht aktivierten [2+2]‐Photocycloaddition unter Verwendung eines Lewis‐Säurekatalysators mit Chiralität am Rh‐Zentrum. Man erhält chirale tricyclische Strukturen mit bis zu vier Stereozentren, darunter ein quartäres. Computer‐Modellierungen decken den Ursprung der beobachteten Regioselektivität auf.